Arthur White Collection, Correspondence from London division via Chris Hanson to Time Press, July 19, 1978. - Hanson, Chris (Time Magazine; Digitized from original print, Valdosta State University Archives and Special Collections, December 1, 2016., 1978)
Correspondence from London division via Chris Hanson to Time Press in reference to the impending birth of the first "test-tube baby" by Lesley and John Brown in Oldham, England in 1978 by doctors Patrick Steptoe and Robert Edwards.
Digitized from original print, Valdosta State University Archives and Special Collections, December 1, 2009.
Keywords: Test tube baby; Arthur White; Chris Hanson; Time Magazine; Time Press; In Vitro Fertilization; IVF; Steptoe-Edwards Fertilization Technique; 1970s; 1978; Lesley Brown; John Brown; Lousie Joy Brown; Oldham General Hospital; Oldham, England; London, England; England; Great Britain; Professor Sir Robert Edwards; Robert Edwards; Patrick Steptoe